Quality Indicators in Pediatric Palliative Care: Considerations for Latin America - Gregorio Zuniga-Villanueva; Jorge Alberto Ramos-Guerrero; Monica Osio-Saldaña; Jessica A. Casas; Joan Marston; Regina Okhuysen-Cawley (MDPI AG, 2021)
Pediatric palliative care is a growing field in which the currently available resources are still insufficient to meet the palliative care needs of children worldwide. Specifically, in Latin America, pediatric palliative care services have emerged unevenly and are still considered underdeveloped when compared to other regions of the world. A crucial step in developing pediatric palliative care (PPC) programs is delineating quality indicators; however, no consensus has been reached on the outcomes or how to measure the impact of PPC. Additionally, Latin America has unique sociocultural characteristics that impact the perception, acceptance, enrollment and implementation of palliative care services. To date, no defined set of quality indicators has been proposed for the region. This article explores the limitations of current available quality indicators and describes the Latin American context and how it affects PPC development. This information can help guide the creation of standards of care and quality indicators that meet local PPC needs while considering the sociocultural landscape of Latin America and its population.